Self-Help Abilities of Children Age 4-5 Years Viewed from Preschool Education - Kusuma, Ayu Rahayu; Mukminin, Amirul (BELIA: Early Childhood Education Papers, 2020)
This study aims to determine the differences in the self-help abilities of children aged 4-5 years viewed from preschool education. The type of research used in this study is a comparative causal study. The populations in this study are all children aged four to five years or were in the kindergarten in Gunungpati, Semarang City where in the population there were children who took different preschool education places. The sampling technique used was purposive sampling technique that is the technique of determining the sample based on certain considerations with a total number taken 192 samples. The data collection method used in this study is the Likert Scale. The data analysis method used is the independent sample t-test. The results of the calculation of the hypothesis can be accepted if the Sig. <0.05. The results show that the value of sig. (2-tailed) is greater than 0.05 which is 0.964 Ëƒ 0.05 so Ha is rejected. Based on these results it shows that there is no difference in the ability of self-help children aged 4-5 years in Gunungpati between children who get a preschool education place either at school or family.